Effect of Autogenous Cortical Bone Grafting in Conjunction with Guided Tissue Regeneration in the Treatment of Intraosseous Periodontal Defects - Keles, Gonca Cayir; Sumer, Mahmut; Cetinkaya, Burcu Ozkan; Tutkun, Ferda; Simsek, S. Burcak (European Journal of Dentistry, 2010)
Objectives: The aim of this clinical trial was to evaluate the additional benefit of using guided tissue regeneration (GTR) with autogenous cortical bone (ACB) grafting versus ACB grafting alone for the regenerative treatment of intraosseous periodontal defects.Methods: Via a split-mouth design, 12 patients with chronic periodontitis (five men, seven women; mean age, 45.3±4.6 years) who had probing pocket depths (PPDs) of ≥6 mm following initial periodontal therapy were randomly assigned to two treatments in contralateral areas of the dentition: a combination of ACB grafting and GTR (with a absorbable membrane of polylactic acid) or ACB grafting alone. The compared parameters were preoperative and 6-month postoperative PPDs, clinical attachment levels (CALs), and radiographic alveolar bone heights.Results: Both treatment modalities resulted in significant changes in the postoperative measurements from the preoperative values (P<.01). The reduction in the PPDs, gain in the CALs, and gain in the radiographic alveolar bone heights were 4.58±1.08, 4.25±1.06, and 5.50±2.24 mm in the patients treated with ACB grafting and GTR and 4.92±1.00, 4.50±0.80, and 5.92±1.83 mm in those treated with ACB grafting alone, respectively. The differences between the treatments were not statistically significant (P>.05).Conclusions: Within the study limitations, both ACB grafting with GTR and ACB grafting alone lead to significant improvements in clinical and radiographic parameters at 6 months postoperatively. The combined approach does not provide any additional benefit for treating intraosseous periodontal defects. (Eur J Dent 2010;4:403-411)
Keywords: Autogenous bone graft; Guided tissue regeneration; Intraosseous defects; Periodontal regeneration